Technostress in the Academic Attraction of University Students in Peru - Quispe Fernández, José Luis; Quispe Fernández, Ursula Isabel; Farias Clavo, Carla Vanessa; Hernández Domínguez, Pablo Ysidoro (Areté, Doctorate in Education Digital Journal, 2024)
The main objective was to determine the action of technostress on academic burnout (AD) in 250 students from a Technological Institute in Lima, Peru. Applied research, with a quantitative, non-experimental, transversal, causal correlational approach, the method was hypothetical - deductive. The RED – technostress scale was used and for academic burnout the Maslach Burnout Inventory (revised versions designed for university students). Using ordinal logistic regression, it was shown that there is a dependence between technostress and academic burnout (Nagelkerke=0.389) up to 38.9%; the objectives and specific hypotheses were confirmed according to the Nagelkerke coefficient (0.387; 0.284; 0.214; 0.189; 0.324). The dimensions that most affect the student population and are linked to technostress were skepticism, addiction and fatigue, and to a lesser extent anxiety and inefficiency. A curricular reform would be needed to develop soft skills, emotional intelligence and transformational leadership for collaborative and team work. Likewise, greater organizational commitment is suggested to prioritize necessary academic load and implement emotional support and socio-affective accompaniment interventions.